ANALISIS POTENSI DAN EFEKTIVITAS PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH - NANANG HERMANTO; ERNANI HADIYATI; DJUNI FARHAN (Jurnal Akademika, 2022)
This study aims to analyze the relationship of each local tax to local revenue, as well as the potential and effectiveness of each local tax. The design of this research is descriptive quantitative research. The results showed during the research period that the Street Lighting Tax, BPHTB, and PBB made a major contribution to Regional Original Revenue for Malang Regency, and for the City of Malang the major contributors were Hotel Tax, Restaurant Tax, Street Lighting Tax, BPHTB and PBB. In the Overlay Analysis, the potential for local taxes in Malang Regency has potential in its contributions, namely Hotel Tax, Restaurant Tax, Entertainment Tax, Advertising Tax, Street Lighting Tax, BPHTB and PBB. Malang City includes Hotel Tax, Restaurant Tax, Entertainment Tax, Advertising Tax, Street Lighting Tax, Parking Tax, BPHTB and PBB which contribute to Regional Original Income. From the analysis that all local taxes are less potential than the overall Regional Original Income, but have a high effectiveness in fulfilling the Regional Revenue Target. It is hoped that the Regional Government can see the Potential and Effectiveness of each Regional Tax to be increased and maximized to contribute to Regional Original Income. Keywords: local tax, potential, effectiveness